Manufacturing method of molded object and molded object
By adjusting the output and scanning speed of the energy beam, the crystals and amorphous substances in the formation area have a high proportion of the crystals and amorphous substances, the problem of difficulty in efficiently removing unnecessary parts in the direct forming method is solved, and the strength and manufacturing efficiency of the product are improved.
Patent Information
- Application Number
- JP2023176434
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2017-10-27
- Filing Date
- 2023-10-12
- Publication Date
- 2025-04-01
- Estimated Expiration
- 2038-10-24
AI Technical Summary
The existing direct forming method is difficult to efficiently remove unnecessary parts while maintaining the strength of the product when manufacturing a three-dimensional structure.
By adjusting the output of the energy beam, the relative position of the surface powder layer and the focus of the energy beam, and the scanning speed, the formation region has a high proportion of crystals and amorphous substances, thereby controlling the mechanical strength of the product.
It is achieved to efficiently remove unnecessary parts in the direct forming method while maintaining the strength of the product, improving the manufacturing efficiency and the mechanical properties of the product.
Smart Images

Figure 0007654742000003 
Figure 0007654742000004 
Figure 0007654742000005
Abstract
Description
[Technical field]
[0001] The present invention relates to a method for producing a shaped object using an inorganic compound powder, and the shaped object, and in particular to a method for producing a three-dimensional shaped object and the three-dimensional shaped object. [Background technology]
[0002] 2. Description of the Related Art Direct fabrication techniques for manufacturing desired objects, particularly three-dimensional objects, by bonding material powder with an energy beam are becoming popular for applications such as creating prototypes in a short period of time or manufacturing a small number of parts.
[0003] Patent Document 1 describes a method for manufacturing an article using the so-called powder bed fusion method. In this method, a powder layer made of a material powder is formed on a substrate, and an energy beam is selectively irradiated to a portion of the powder layer that corresponds to the cross section of the article, to sinter the powder, and a series of steps are repeated. In the repetition of this series of steps, the portion sintered earlier and the portion sintered later are bonded to each other, and finally, the powder of the non-sintered portion and the unnecessary portion of the sintered portion are removed to obtain the desired article.
[0004] Direct manufacturing methods such as powder bed fusion do not require the use of molds or cutting out from ingots, and can produce 3D objects with high accuracy in a short time because they can be manufactured directly from powder. In addition, they have the advantage that they can be manufactured based on 3D data created using design tools such as 3D CAD, making it easy to change the design and capable of manufacturing 3D objects with complex and detailed shapes.
[0005] On the other hand, the surface of a 3D object produced by the direct printing method becomes uneven because unwanted material powder adheres and bonds to the surface due to the heat transferred from the part irradiated with the energy beam. Therefore, in order to obtain a 3D object with a smooth surface, it is necessary to process the surface during or after printing.
[0006] Patent Document 2 discloses a method for reducing the amount of material powder that adheres and bonds in a direct molding method using metal powder, thereby shortening the surface cutting time. However, this method has poor cutting efficiency because it cuts a material with high mechanical strength similar to that of a three-dimensional object. Patent Document 2 also discloses a method for irradiating an energy beam onto the surface of a three-dimensional object to temporarily soften the surface before cutting. Since the material powder described in Patent Document 2 is metal, it is possible to soften the surface even with a low-energy energy beam, but it is difficult to apply this method to inorganic compounds such as ceramics, which have high melting temperatures.
[0007] In addition, the heat applied by the energy beam to the first powder layer on the substrate reaches the substrate, so the sintered part is bonded to the substrate. Furthermore, when manufacturing an article with an overhang, it is necessary to form a support to prevent bending or falling due to gravity.
[0008] When the substrate or support is no longer needed, it is removed from the 3D object by machining such as cutting. In the case of modeling using inorganic compound powders such as ceramics, the mechanical strength of the object is high, so it takes a lot of time to remove the support and separate it from the substrate. [Prior art documents] [Patent documents]
[0009] [Patent Document 1] Special Publication No. 1-502890 [Patent Document 2] JP 2008-291315 A Summary of the Invention [Problem to be solved by the invention]
[0010] The present invention has been made to address such problems, and provides a method for manufacturing a molded object in a direct molding process, which is capable of efficiently removing unnecessary portions of the molded object while achieving the desired strength of the object. [Means for solving the problem]
[0011] A method for producing a shaped object according to one aspect of the present invention includes the steps of: A method for manufacturing a shaped object, the method comprising the steps of: forming a powder layer made of a material powder including an inorganic compound powder; and irradiating a predetermined region on a surface of the powder layer with an energy beam to melt and solidify the material powder, the method comprising the steps of: In the process of melting / solidifying the material powder, regions having a high amorphous content and regions having a high crystalline content are created by changing at least one of the output of the energy beam, the relative position between the surface of the powder layer and the focus of the energy beam, and the scanning speed of the energy beam.
[0012] A method for producing a shaped object according to another aspect of the present invention includes the steps of: A method for manufacturing a shaped object, the method comprising the steps of: forming a powder layer made of a material powder including an inorganic compound powder; and irradiating a predetermined region on a surface of the powder layer with an energy beam to melt and solidify the material powder, the method comprising the steps of: The process of melting / solidifying the material powder includes a step of irradiating the energy beam under conditions whereby the ratio D / L, which is the ratio of the width L in a direction perpendicular to the scanning direction to the depth D from the surface of the solidified portion formed when the energy beam is scanned once in one direction, is greater than 1.0, thereby forming a region with a high amorphous content, and a step of irradiating the energy beam under conditions whereby the D / L is 1.0 or less, thereby forming a region with a high crystalline content.
[0013] A shaped object according to another aspect of the present invention is a shaped object containing an inorganic compound, characterized in that it has a first region having a high crystalline proportion and a second region having a high amorphous proportion, and at least a portion of the surface of the shaped object includes the second region. Effect of the Invention
[0014] According to the present invention, it is possible to provide a method for manufacturing a shaped object in a direct manufacturing process, which is capable of efficiently removing unnecessary portions of the shaped object while achieving a desired strength of the shaped object. [Brief description of the drawings]
[0015] [Figure 1] 1 is a schematic diagram showing a process flow in a method for manufacturing a shaped object according to the present invention. [Diagram 2] 1 is a schematic cross-sectional view showing an embodiment of a method for producing a shaped object of the present invention. [Diagram 3] 1A is a diagram showing the shape of a molten portion formed by scanning a powder layer once in one direction with an energy beam, in a cross section perpendicular to the beam scanning direction. FIG. [Figure 4] 5A to 5C are schematic cross-sectional views illustrating a process for forming a shaped object and a process for treating the shaped object in one embodiment of the method for producing a shaped object of the present invention. [Diagram 5] 5A to 5C are schematic cross-sectional views illustrating an example of a manufacturing process for the embodiment of the shaped object of the present invention shown in FIGS. 4(a) and 4(b). [Figure 6] FIG. 2 is a schematic perspective view showing a laser irradiation process in Example 1 of the present invention, and a schematic perspective view showing a shaped object in Example 1. [Figure 7] 1 is a graph showing the relationship between the amount of heat input and the proportion of crystalline matter in Examples 1 to 4 of the present invention. [Figure 8] 1 is a graph showing the relationship between the amount of heat input and the proportion of crystalline matter in Examples 5 to 8 of the present invention. [Figure 9] 1 is an SEM image showing a polished surface of a cross section of the object of Example 1. [Figure 10] 3A and 3B are conceptual diagrams for explaining focused and unfocused states of a laser. [Figure 11] FIG. 2 is a schematic diagram illustrating a configuration of a three-dimensional modeling apparatus. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0016] (3D printing equipment) First, a three-dimensional modeling apparatus 100 used in this embodiment will be described with reference to FIG. The modeling table 101 is a table for mounting the plate 102, and also serves as the bottom surface of the modeling container 103. The modeling table 101 has pins (not shown), which are fitted into pin holes (not shown) in the plate 102 to position the plate 102. It is preferable that the plate 102 is fixed to the modeling table 101 by screws. Note that the plate does not necessarily have to be plate-shaped as long as it functions as a support base when forming a three-dimensional object, and the method of positioning and fixing the plate to the modeling table is not limited to this example. The modeling table 101 is supported by a vertical movement mechanism 104 so as to be vertically movable.
[0017] Adjacent to the modeling table 101, a powder supply container 106, a roller 107, a moving guide 108 for moving the roller 107, a laser light source 109, a scanner 110, and a condenser lens 111 are arranged. The powder supply container 106 is a device for storing powder 113 for modeling and for adjusting the supply amount of the powder 113 according to the thickness of the powder layer to be deposited in the modeling container 103. The supply amount of the powder 113 can be adjusted by the lift amount of the vertical movement mechanism 105. The roller 107 is supported by the moving guide 108 so as to be movable in the horizontal direction, and moves the modeling powder from the powder supply container 106 to the modeling container 103, and forms a powder layer of a predetermined thickness while leveling the surface. The laser light source 109, the scanner 110, and the condenser lens 111 constitute an irradiation optical system for locally and selectively irradiating the raw material powder layer with laser light 115.
[0018] The control unit 112 is a computer for controlling the operation of the 3D modeling apparatus 100, and includes a CPU, a memory, a storage device, an I / O port (input / output unit), and the like. The memory is a random access memory (RAM) or a read-only memory (ROM). The storage device is a hard disk drive, a disk drive, a magnetic tape drive, or the like, and stores a program that realizes the processing of the flowcharts described below. The I / O port is connected to an external device or a network, and can input and output data required for three-dimensional printing between an external computer and the controller 112. The data required for three-dimensional printing includes shape data of the object to be manufactured, information on materials used for printing, and shape data of each sintered layer divided into multiple layers that are continuous in a predetermined direction, i.e., slice data. The slice data may be received from an external computer, or may be created by the CPU in the controller 112 based on the shape data of the printing model and stored in the memory. The CPU causes the 3D printing apparatus 100 to perform each process described below by loading a program stored in the storage device into the memory and executing the program.
[0019] The control unit 112 is connected to each part such as the vertical movement mechanism 104 of the modeling table, the vertical movement mechanism 105 of the bottom surface of the powder supply container 106, the rollers 107, the laser light source 109, the scanner 110, and the focusing lens 111, and controls the operation of these parts to perform modeling-related processing.
[0020] The process flow of the method for producing a shaped object of the present invention is shown in Fig. 1. Hereinafter, an embodiment of the present invention will be described according to the process flow of Fig. 1, however, the present invention is not limited to the following specific example.
[0021] (Outline of the process) First, the entire method for manufacturing a shaped object will be described with reference to Fig. 1, and then the characteristic parts of the present invention will be described. Each step of the method for manufacturing a shaped object described below is realized by a CPU expanding a program stored in a storage device into a memory and executing the program.
[0022] First, three-dimensional shape data of an article (model) to be modeled is acquired (step S1). The three-dimensional shape data of the article is input from a 3D CAD or a three-dimensional scanner via an I / O port of the control unit 112 and stored in memory.
[0023] Next, based on the three-dimensional shape data of the article, the three-dimensional shape of a support that supports the structure when the structure is formed by a three-dimensional printing device is designed (step S2). In the present invention, the structure corresponds to the three-dimensional shape data of the printing model, and the support corresponds to a portion added to assist in printing the structure. Specifically, the support is a structure that facilitates separation of the structure from the plate after printing is completed, or a structure that supports the shape of the structure during printing when the structure has a hollow or overhanging shape.
[0024] Subsequently, amorphous / crystalline information is given (step S3). Specifically, information is given to the three-dimensional shape data in which the support is added to the modeling model as to which region is to be the region with a high amorphous content and which region is to be the region with a high crystalline content. As will be described in detail later, the region including the boundary between the support and the structure and the region including the first layer formed on the plate of the support provided between the structure and the plate are designated as the region with a high amorphous content, and the other parts are designated as the region with a high crystalline content. Alternatively, it is also preferable to designate not only a part of the support but also a region including the surface of the structure as the region with a high amorphous content.
[0025] The amorphous / crystalline information can be added by inputting it to the control unit 112 via an I / O port. For example, the user may operate a mouse to set a region for three-dimensional shape data in which a support is added to a modeling model displayed on a display unit connected to the I / O port. Alternatively, the user may select a mode in which it is previously set which parts are to have a high amorphous or crystalline ratio, such as a mode in which a region including a boundary with the support structure is set as a region with a high amorphous ratio and other parts are set as a region with a high crystalline ratio.
[0026] The region with a high amorphous content or a region with a high crystalline content is preferably specified to have a size of 100 μmφ or more in the stacking direction and in-plane direction, and more preferably a size of 200 μmφ or more, depending on the irradiation diameter of the energy beam and the stacking pitch. Next, the three-dimensional printing device 100 creates shape data for each layer required for stacking and forming the model, that is, slice data for the support body and the structure (step S4).
[0027] Steps S1 to S4 may be created by the CPU of the control unit based on the three-dimensional shape data of the modeling model and the support and stored in the RAM, or may be executed by an external computer and received via an I / O port. In addition, when three-dimensional shape data with a support body added and slice data are available as modeling data, each step can be omitted.
[0028] Next, the plate 102 is positioned and fixed (step S5) to the three-dimensional modeling apparatus 100. Fixing of the plate may be performed prior to steps S1 to S3.
[0029] Next, a support is formed on the plate 102 (step S6). After forming one powder layer, the 3D printing device 100 irradiates the powder layer with laser light according to slice data to form a solidified portion. Once the formation of the support is complete, a structure that is a part corresponding to the model is formed on the support (step S7). Once the formation is complete, the plate 102 is removed from the 3D printing device 100 (step S8), and the structure 114 and the plate 102 are separated (step S9). After that, post-processing (step S10) is performed as necessary to obtain an article corresponding to the model.
[0030] 2(a)-(h) are schematic cross-sectional views showing steps S5-S9 in the powder bed fusion bonding method, which is a preferred embodiment of the method for producing a three-dimensional object of the present invention. A material powder 301 containing an inorganic compound powder is used for the production. First, a powder layer 302 made of the material powder 301 and having a predetermined thickness is formed on a substrate 320 using a roller 352 (FIGS. 2(a) and 2(b)). Based on slice data generated from the three-dimensional data of the modeling model, a step is performed (FIG. 2(c)) in which an energy beam 501 emitted from an energy beam source 500 is irradiated while scanning the surface of the powder layer 302 to selectively melt / solidify the material powder. As a result, a region (modeled portion) 300 where the material powder 301 is melted and solidified and a region (non-modeled portion) 303 where the material powder remains in a powder state are formed (FIG. 2(c)). Next, the stage 351 is lowered to a position that is one powder layer thick below the upper edge of the modeling container 353, and a new powder layer 302 is formed to cover the modeling portion 300 and the non-modeling portion 303 (FIG. 2(d)). A series of steps, including the step of forming the powder layer 302 and the step of selectively melting / solidifying the material powder by irradiating the material powder while scanning it with an energy beam 501, are repeated once or multiple times (FIG. 2(e)). Then, the modeling portions formed from the respective powder layers are integrated to form the modeling portion 304 (FIG. 2(f)).
[0031] Next, the material powder in the non-melted / unsolidified region (non-modeled portion) 303 is removed (FIG. 2(g)), and if necessary, the modeled object 306 is subjected to post-processing such as separation from the substrate 320 and removal of the support 308 to obtain a processed modeled object 307 (FIG. 2(h)). As will be described in more detail later, in the figure, the filled-in pattern of modeled portion 300 indicates an area with a high amorphous content, and the filled-in pattern of modeled portion 304 indicates an area with a high crystalline content.
[0032] (Material powder) The material powder used in the present invention is preferably a ceramic powder. Here, ceramics refers to solid inorganic compounds other than metals, and the solid bonding state (crystalline or amorphous) does not matter. In this specification, inorganic compounds refer to oxides, nitrides, oxynitrides, carbides, or borides containing one or more elements selected from the group of elements from Groups 1 to 14 of the Periodic Table excluding hydrogen, plus antimony and bismuth. Examples of ceramic powders that can be used as material powders include metal oxides, nonmetal oxides, nitrides, fluorides, borides, chlorides, and sulfides. The material powder may be composed of one type of inorganic compound, or may be a mixture of two or more types of inorganic compounds. In addition, ceramic powder means a powder mainly composed of ceramics, and does not exclude the inclusion of powders other than ceramics.
[0033] A three-dimensional object (hereinafter simply referred to as an object) made primarily of ceramics has a higher mechanical strength than resin or metal.
[0034] The main component of the ceramic powder is preferably an oxide. Compared to other inorganic compounds, oxides have fewer volatile components, so stable melting can be achieved, and it is easy to create regions with a high crystalline content and regions with a high amorphous content. Representative oxides include aluminum oxide, zirconium oxide, magnesium oxide, silicon oxide, and mixtures or compounds of these.
[0035] Furthermore, it is more preferable that the ceramic powder contains aluminum oxide and zirconium oxide, or aluminum oxide and rare earth oxide. These ceramic powders have a lower melting point than general ceramics, so the powder can be melted even with a low-output energy beam. If the material powder is not melted enough, a molded object cannot be formed, so there is a lower limit to the output of the energy beam. However, by using the above-mentioned ceramic powder, the lower limit is reduced, and the usable range of the output value is expanded. This makes it easier to control the ratio of crystalline to amorphous. In addition, since molding can be performed with a low output, unnecessary adhesion and bonding of the material powder due to heat transfer from the energy beam irradiation part is suppressed, and molding accuracy is further improved.
[0036] The crystalline material to be molded does not need to be composed of a single phase, and preferably has a phase-separated structure consisting of two or more phases. By having a phase-separated structure consisting of two or more phases, the extension of cracks is suppressed, and additional functions such as further improving the mechanical strength of the molded product are exhibited. Examples of ceramic powders that form a phase-separated structure consisting of two or more phases include a eutectic mixture of aluminum oxide and zirconium oxide, and a mixture of aluminum oxide and rare earth oxide.
[0037] In addition, when the energy beam is a laser beam, sufficient energy absorption in the material powder suppresses the spread of heat in the powder layer and makes it localized, reducing the impact of heat on non-printing areas, improving printing accuracy. For example, when using an Nd:YAG laser, Tb4O7 and Pr6O 11 From the above viewpoints, more suitable material powders include Al2O3-ZrO2, Al2O3-Gd2O3, Al2O3-Y2O3, Al2O3-Tb4O7, ZrO2-Tb4O7, Y2O3-Tb4O7, and Gd2O3-Tb4O7, and even more suitable material powders include Al2O3-Gd2O3-Tb4O7, Al2O3-ZrO2-Tb4O7, and Al2O3-Y2O3-Tb4O7.
[0038] In addition, the material powder in the present invention may contain a small amount (10 parts by weight or less per 100 parts by weight of the inorganic compound powder) of resin, metal, etc. in addition to the inorganic compound powder in order to adjust the fluidity of the powder and the performance of the final molded object.
[0039] (Formation of powder layer) An example of a preferred embodiment of the powder layer forming step in the present invention will be described. In the powder layer forming step, a powder layer is formed using a material powder containing an inorganic compound powder. In the step of forming a first powder layer on the substrate 320, a powder layer 302 having a predetermined thickness is formed as shown in FIG. 2(b). In the step of forming the second and subsequent powder layers, a new powder layer 302 is formed on the powder layer 302 formed in the previous step and on the modeling section 300 (FIG. 2(d)). The method of forming the powder layer 302 is not particularly limited. It is preferable to form the powder layer 302 while defining the layer thickness with a roller 352 or a blade as shown in FIG. 2(a).
[0040] Although the powder bed fusion method has been described above, the modeling method according to the present invention is not limited to this. A model may be produced by a directed energy deposition modeling method (so-called cladding method) in which, instead of forming a powder layer, material powder 301 is sprayed from a nozzle to the irradiation position of the energy beam and the material powder is piled up on the substrate 320 or the modeling surface of the modeling unit 300.
[0041] (Melting / solidification of material powder) The step of irradiating a predetermined area on the surface of a powder layer with an energy beam to melt and solidify the material powder (hereinafter, abbreviated as melting / solidifying step) in the present invention will be described based on a preferred embodiment.
[0042] In the melting / solidifying process, the material powder is melted / solidified by irradiating it with an energy beam according to the slice data. When the material powder is irradiated with the energy beam, the material powder absorbs the energy, which is converted into heat and melts the material powder. When the irradiation of the energy beam is completed, the molten material powder is cooled by the surrounding area adjacent to the molten area and solidifies.
[0043] As shown in FIG. 2(c), when the surface of the powder layer 302 formed on the substrate 320 is irradiated with an energy beam 501 while being scanned by a scanning mirror, the powders in the area irradiated with the energy beam 501 melt / solidify to form the modeled portion 300. If the output of the energy beam 501 is adjusted so that the heat given to the material powder reaches the interface between the substrate 320 and the powder layer 302, the substrate 320 and the modeled portion 300 are bonded to each other. Also, as shown in FIG. 2(d) and 2(e), when the energy beam 501 is irradiated to the powder layer 302 formed on the modeled portion 300, a new modeled portion 304 is formed. At this time, the heat given to the material powder reaches the interface between the previously formed modeled portion 300 and the later formed powder layer 302, so that the previously formed modeled portion 300 and the newly formed modeled portion 304 are bonded to each other. By repeating this series of melting / solidification processes, the shaped parts formed in each powder layer are bonded to each other to form an integrated object (Figure 2(f)).
[0044] The energy beam to be used is selected from a light source with an appropriate wavelength, taking into consideration the absorption characteristics of the material powder. In order to perform high-precision modeling, it is preferable to use a laser beam or electron beam with a narrow beam diameter and high directivity. When the material powder contains oxide powder, the laser beam can be a YAG laser or fiber laser with a wavelength of 1 μm, or a CO2 laser with a wavelength of 10 μm.
[0045] In the present invention, when the energy beam is irradiated in the melting / solidifying process, at least one of the relative position between the surface of the powder layer and the focus of the energy beam, the output of the energy beam, and the scanning speed is changed according to the irradiation area. In other words, the slice data includes information on which area is to be determined as an area with a high amorphous content and which area is to be determined as an area with a high crystalline content.
[0046] By irradiating the energy beam while changing at least one of the relative position between the surface of the powder layer and the focus of the energy beam, the output of the energy beam, and the scanning speed, the solidification rate of the molten material, i.e., the cooling rate, can be changed, and the mechanical strength of the molded part can be changed. Specifically, a faster cooling rate results in a region with a relatively low mechanical strength and a high proportion of amorphous matter, while a slower cooling rate results in a region with a relatively high mechanical strength and a high proportion of crystalline matter.
[0047] The shape of the molten part is greatly affected by the cooling rate. Figures 3(a) and (b) show the shape of the molten part (i.e. solidified part) in a cross section perpendicular to the beam scanning direction, formed by scanning the powder layer once in one direction with an energy beam. The molten width (solidified width) in the direction perpendicular to the scanning direction is L, and the molten depth (solidified depth) from the surface in the irradiation direction is D.
[0048] As shown in Figure 3(a), when the ratio of depth D to width L, D / L, is greater than 1.0 (shape that is sharp in the depth direction), the heat in the molten part is more likely to dissipate in all directions, as shown by the arrows at the bottom of the figure, and cooling becomes faster, so the material is likely to become amorphous. On the other hand, as shown in Figure 3(b), when the ratio of D / L is 1.0 or less (shape that is shallow and blunt (i.e., gentle)), as shown by the arrows at the bottom of the figure, heat transfer is reduced and cooling becomes slower, so the material is likely to become crystalline. In other words, the cooling speed of the molten part depends heavily on D / L.
[0049] D / L, which represents the shape of the molten part, can be adjusted by the relative position between the surface of the powder layer and the focus of the energy beam. When the energy beam is irradiated while being focused on the surface of the material powder, the intensity profile within the energy beam becomes steeper and D / L becomes larger. As a result, the cooling rate becomes faster and the solidified part becomes an area with a high proportion of amorphous matter.
[0050] The shape of the molten part is also affected by the power of the energy beam. Increasing the power of the irradiated energy beam increases D / L and the amount of heat input per unit area. Since the cooling rate is more affected by D / L than by the amount of heat input per unit area, when the power of the energy beam is high, D / L increases and the cooling rate increases, making it possible to form a region with a high proportion of amorphous material.
[0051] The cooling rate can also be adjusted by the scanning speed of the energy beam. When D / L is constant, if the scanning speed of the energy beam is increased, the amount of heat input per unit time decreases, so the cooling rate also increases, and the solidified part tends to become amorphous. If the scanning speed of the energy beam is slowed, the amount of heat input per unit time increases, so the cooling rate also slows, and the solidified part tends to become more crystalline.
[0052] Therefore, the regions with a high crystalline content and the regions with a high amorphous content can be created by changing either the power of the energy beam, the relative position between the surface of the powder layer and the focus of the energy beam, or the scanning speed, or by combining these parameters.
[0053] If the output of the energy beam is too small, the strength is insufficient and some of the material remains unmelted. Conversely, if the output of the energy beam is too large, the material may melt too much and the molding accuracy may not be obtained. In order to create regions with a high crystalline content and regions with a high amorphous content while obtaining molding accuracy, it is preferable to change one or both of the scanning speed of the energy beam and the relative position between the surface of the powder layer and the focus of the energy beam. In addition, the scanning speed is related to the time required to form a molded object. When changing the scanning speed to form a region with a high crystalline content, the scanning speed must be reduced, which may slow down the molding speed. Therefore, it is particularly preferable to not change the scanning speed and to change the relative position between the surface of the powder layer and the focus of the energy beam to create regions with a high crystalline content and regions with a high amorphous content, as this does not significantly affect the molding speed.
[0054] The conditions for realizing a D / L preferable for forming a region with a high crystalline content and a region with a high amorphous content differ depending on the composition and particle size of the material powder, the configuration of the three-dimensional printing device, etc. Therefore, conditions are determined in advance for the output of the energy beam, the relative position between the printing surface and the focus of the energy beam, and the scan speed for printing a region with a high crystalline content and a region with a high amorphous content, respectively.
[0055] In the case of DIFA, it is also possible to create regions with different ratios of amorphous and crystalline by changing the cooling rate of the molten part. Specifically, as in the case of powder bed fusion bonding, the desired conditions can be derived by changing at least one of the power of the energy beam, the relative position between the building surface and the focal point of the energy beam, and the scanning speed according to the region.
[0056] In the present invention, the crystalline and amorphous materials formed by irradiation with an energy beam are formed from the same inorganic compound powder, and therefore have approximately the same composition.
[0057] Input heat per unit area Q [J / mm2 ] can be calculated from the power P [W], irradiation diameter 2r [mm], and scan speed v [mm / s] (irradiation time T [s] when the scan speed is 0). If the irradiation diameter is assumed to be a point, the time required for the irradiation point at a scan speed v [mm / s] to pass through a unit length of 1 mm is 1 / v [s]. Therefore, the input heat Q [J / mm 2 ] is calculated using the formula Q=P / (πr 2 v) can be used. When the scan speed is 0, Q can be calculated using the irradiation time T [s] as follows: Q = PT / (πr 2 ) In the case of electron beams, P = IE when the accelerating voltage E [kV] and the beam current I [mA] are used, so Q = IE / (πr 2 v). When the scan speed is 0, Q = IET / (πr 2 )
[0058] The case where an energy beam is irradiated to the powder layer surface in a focused or unfocused state to realize the creation of a region with a high crystalline content and a region with a high amorphous content will be described in detail with reference to the conceptual diagram of FIG. 10. By changing the ratio of focused / unfocused, the shape of the molten part changes, and the cooling rate can be controlled. For example, the laser beam 180 reaches the powder layer with a high energy density in the center of the beam due to the optical system (including fibers, lenses, etc.) included in the laser beam source. The focused state refers to a state in which the surface of the powder layer is within the focal depth of the laser beam 180, that is, a state in which the laser beam is irradiated to the surface of the powder layer near the A-A' cross section in FIG. 10. The unfocused state refers to a state in which the focus position is shifted with respect to the powder layer in order to obtain a desired laser beam intensity profile on the powder layer, which will be described in detail later. That is, the out-of-focus state in the present invention means that a desired laser beam intensity profile can be realized, and includes a state in which the surface of the powder layer is simply displaced from the focal position determined by the focal length of the focusing optical system of the device being used. As shown in Fig. 10, the out-of-focus state is a state in which the laser beam is irradiated onto the surface of the powder layer at a B-B' cross section that is separated in either the up or down direction from the A-A' cross section that passes through the focal point of the laser beam.
[0059] When a laser beam is irradiated onto a powder layer in a focused state, the energy intensity profile of the beam spot focused on the powder layer becomes a steep distribution, and D / L becomes large, which results in a faster cooling rate and a higher proportion of amorphous material.
[0060] On the other hand, when the powder layer is irradiated with a laser beam in a defocused state, the energy intensity profile of the beam spot becomes a gentle distribution, which is different from the focused state, and rapid cooling of the molten part after laser irradiation can be avoided. Therefore, the formation of amorphous matter due to rapid cooling can be suppressed, and as a result, a ceramic object with a high proportion of crystalline matter can be obtained.
[0061] Next, a method for irradiating the laser beam in an unfocused state will be described. For example, in the case of an apparatus that is set to be in focus on the surface of the powder layer, it is possible to achieve an unfocused state on the surface of the powder layer by changing the height of the stage in the vertical direction.
[0062] Alternatively, rather than changing the stage height, the energy intensity profile of the beam spot may be made to have a gentler shape by driving an optical system included in the laser beam source or by changing an optical system arranged in the optical path, thereby realizing a defocused state.
[0063] In order to form a region with a high proportion of crystalline, the ratio D / L of the width (L) of the melting of the solidified part to the depth (D) of the melting is preferably 1.0 or less, and more preferably 0.2 to 0.7 (0.2≦D / L≦0.7). When the laser beam is irradiated in a defocused state, it is possible to make D / L 1.0 or less, and 50% or more by volume of the solidified part can be made crystalline. By increasing the degree of defocusing, it is possible to further reduce D / L. By making D / L 0.7 or less, 80% or more by volume of the solidified part can be made crystalline. If D / L is less than 0.2, melting in the depth direction is insufficient, and bonding with the lower layer may be poor during stacking. Therefore, D / L is preferably 0.2 or more.
[0064] Conversely, if D / L is greater than 1.0, the rapid cooling during solidification makes it easier for amorphous material to form. By irradiating a laser beam in a focused state, it is possible to increase D / L to greater than 1.0, and 50% or more by volume of the solidified portion can be made amorphous. A more preferable D / L for increasing the proportion of amorphous material is 1.2 or more. When D / L is 1.2 or more, 70% or more by volume of the solidified portion can be made amorphous. D / L can also be changed by the output of the energy beam, such as the laser output.
[0065] When a region with a high amorphous content and a region with a high crystalline content are mixed in one powder layer, it is preferable to form the entire region of one of the regions in the layer, and then change the irradiation conditions to form the entire region of the other region. That is, in the process of melting / solidifying the material powder that forms the powder layer, a first scanning stage is provided in which conditions for forming a region with a high crystalline content are set. Then, in order to form a region with a high amorphous content, a second scanning stage is provided in which at least one of the conditions of the output of the energy beam, the relative position between the modeling surface and the focus of the energy beam, and the scanning speed of the energy beam is set different from that of the first scanning stage. The order of the first scanning stage and the second scanning stage may be either first. By performing such modeling, it is possible to efficiently perform modeling without frequently changing the irradiation conditions of the energy beam.
[0066] (substrate) The material of the substrate used in the present invention can be appropriately selected from materials such as metals and ceramics that are commonly used in the production of shaped objects, taking into consideration the use of the shaped object and the production conditions.
[0067] (modeled object) The shaped object in the present invention is formed by carrying out the powder layer formation step and the melting / solidification step once or multiple times, and has a region with a relatively high mechanical strength and a region with a relatively low mechanical strength. Specifically, the main part of the shaped object is shaped to have a relatively high mechanical strength, and the boundary between the part to be removed and the part not to be removed by processing the shaped object and the surface part of the part not to be removed are shaped to have a relatively low mechanical strength. This makes it possible to efficiently remove the unnecessary part of the shaped object in the processing step of the shaped object.
[0068] The relative mechanical strength of each part of a molded object can be investigated from the unevenness that occurs when the molded object is mechanically or chemically polished. In the molded object, areas with relatively high mechanical strength (hereinafter referred to as the first area) become convex after polishing, while areas with relatively low mechanical strength (hereinafter referred to as the second area) become concave after polishing. Whether an area is relatively concave or convex can be investigated, for example, using a three-dimensional measuring device, an optical microscope, or a scanning electron microscope (SEM). The absolute value of the mechanical strength of parts of the molded object can be investigated by performing an indentation test or the like on each part.
[0069] When forming the first layer modeling portion 300 on the substrate 320 (FIG. 2(c)), the energy beam is irradiated under conditions that make the cooling rate of the molten portion relatively fast. In other words, when modeling the first layer on the substrate 320, the energy beam is irradiated under conditions that make D / L exceed 1.0. Then, the surface of the substrate 320 melts deeply in accordance with the shape of the molten portion, and the bond between the substrate 320 and the first layer becomes strong. By strengthening the bond between the substrate 320 and the first layer, it is possible to prevent the modeled object 306 from peeling off from the substrate 320 due to stress applied to the interface between the substrate 320 and the modeled object during the modeling process.
[0070] Then, a second region (modeling portion 300) having a relatively low mechanical strength is formed between the modeled object 306 and the substrate 320. This allows efficient separation of the modeling portion 304, which is a structure, from the substrate 320 in the process of processing the modeled object 306. In addition, when the modeled object 306 includes the support 308 (FIG. 2(g)), modeling is performed by changing the cooling rate of the molten part depending on the location. Specifically, a first region (modeling portion 304) is provided in a region that is to become a structure and requires high mechanical strength by irradiating the energy beam under conditions where D / L is 1.0 or less so that the cooling rate of the molten part is relatively slow. Then, a second region is provided at least in a region that is the boundary between the modeling portion 304, which is a structure, and the support 308 by irradiating the energy beam under conditions where D / L is greater than 1.0 so that the cooling rate of the molten part is relatively fast. As a result, in the treatment step of the shaped object 306, the support 308 can be efficiently removed to obtain the shaped portion 304, which is a structure. Naturally, almost the entire region that becomes the support 308 may be made the second region.
[0071] When processing the surface of the molded object in the processing step of the molded object, the energy beam is irradiated under the condition that D / L exceeds 1.0 so that the cooling rate of the molten part in the region near the surface of the structure becomes relatively fast. Then, as shown in FIG. 4(a), it is preferable to provide a second region in a portion including the surface of the molded part 304 (region surrounded by a dashed line), which is the structure. Then, the first region is provided in the molded part 304, which is the main part of the structure, by irradiating the energy beam under the condition that D / L is 1.0 or less. As a result, in the processing step of the molded object 306, the surface of the structure can be efficiently cut and polished to a mirror finish (FIG. 4(b)). An example of the molding process in this case will be outlined with reference to FIGS. 5(a) to 5(h).
[0072] First, a first powder layer 302 is formed on a substrate 320 (FIGS. 5(a) and (b)), and then an energy beam 501 is irradiated onto a predetermined area on the surface of the powder layer 302 to melt / solidify the powder and form a second region, which is a modeled portion 300, having a high amorphous content (FIG. 5(c)). The second region, which is a modeled portion 300, may be formed in multiple layers as necessary.
[0073] Thereafter, a powder layer 302 is formed, and a laser beam is irradiated to provide a second region in the area including the part that will become the surface of the molded object 306 and the part that will become the surface of the structure, and a first region with high mechanical strength in the molded part 304, which will be the main part of the structure.
[0074] This series of steps is repeated one or more times (FIGS. 5(d)-(f)), forming a molded object 306 in which the molded portions formed from the powder layers are integrated (FIG. 5(f)). Next, the material powder in the unmelted / unsolidified regions (non-molten portions) is removed (FIG. 5(g)), and post-processing is performed as necessary, such as separating the molded object 306 from the substrate 320 or partially removing the second region from the surface of the molded portion 306, to obtain a structure 307 (FIG. 5(h)).
[0075] The object is composed of crystalline and amorphous materials. Crystalline refers to a solid material that has a crystal structure. Amorphous refers to a solid material that is assembled without forming crystals. Whether it is crystalline or amorphous can be determined by X-ray diffraction, electron diffraction, etc. In particular, by using an electron backscatter diffraction (EBSD) detector attached to an SEM, it is easy to determine whether it is crystalline or amorphous. If the EBSD detector detects the Kikuchi pattern, it can be determined that the material is crystalline, and if it does not, it can be determined that the material is amorphous.
[0076] The second region of the molded object is mainly made of amorphous. Even if the second region contains less than 30% by volume of crystalline material in addition to the amorphous material, the effect of the present invention can be sufficiently obtained. In other words, 70% by volume or more of the second region is amorphous. When the crystalline material has a phase separation structure consisting of two or more phases, the interface between the phases (phase boundary) is amorphous where the Kikuchi pattern is not detected, but when deriving the volume ratio of the crystalline material, the volume of the phase boundary is also included in the volume of the crystalline material. The volume ratio of the amorphous material to the crystalline material may be considered to be the same as the area ratio of the amorphous material to the crystalline material derived by X-ray diffraction or electron beam diffraction of the cross section of the molded object. The amorphous material has weaker bonds between atoms than the crystalline material, and therefore has lower mechanical strength than the crystalline material. By having a high proportion of amorphous material in the second region, it is possible to efficiently process unnecessary parts in the processing step of the molded object, and to obtain a molded object having high molding accuracy and high mechanical strength.
[0077] According to the method for producing a three-dimensional object of the present invention, the cooling rate of the molten part is changed by changing at least one of the relative position between the surface of the powder layer and the focal point of the energy beam, the output of the energy beam, and the scanning speed according to the irradiation area, thereby changing the ratio of crystalline to amorphous parts in desired parts of the object, and controlling the mechanical strength for each area.
[0078] Specifically, if the cooling rate of the molten portion is fast, the proportion of amorphous material with relatively low mechanical strength in the molded product will be high, and if the cooling rate is slow, the proportion of crystalline material with relatively high mechanical strength will be high. As mentioned above, the shape of the molten portion has a large effect on the cooling rate. If the shape of the molten portion is deep and sharp, the cooling rate will be fast and it will tend to become amorphous. If the shape of the molten portion is shallow and blunt, the cooling rate will be slow and it will tend to become crystalline. The shape of the molten portion can be adjusted by the relative position between the surface of the powder layer and the focus of the energy beam and the output of the energy beam.
[0079] The cooling rate can also be adjusted by the amount of heat input per unit area. Therefore, when it is desired to precisely control the ratio of crystalline to amorphous matter, it is preferable to adjust the amount of heat input per unit area by changing the scanning speed after adjusting the output and focal position of the energy beam to constant values.
[0080] (Processing of objects) In processing the molded object, the material powder from the non-printed parts is removed, and then the support (unnecessary part) included in the molded object is removed. By removing and recovering the unsolidified material powder before removing the support, the removed debris is not mixed into the material powder, and the recovered material powder can be reused to form the powder layer. After removing the unnecessary parts, the processing debris adhering to the surface can be removed by cleaning or the like to obtain a processed molded object.
[0081] The processing of the object may be carried out multiple times in the process of obtaining the desired three-dimensional object, such as by forming a powder layer again on the processed object, irradiating the powder layer with an energy beam to form a new object integrated with the processed object, and then processing the object again.
[0082] In processing the shaped object, it is preferable that the support body of the shaped object (region to be removed) includes a region (second region) having a relatively low mechanical strength. Since such a region has a relatively low mechanical strength, the unnecessary portion can be removed efficiently. When removing the unnecessary portion, the effect of the present invention can be sufficiently obtained as long as the area to be processed by cutting, cutting, polishing, chemical etching, etc. is configured as the second region. Therefore, only a part of the unnecessary portion may be the second region.
[0083] For example, when a three-dimensional object is formed on a substrate, it is preferable to provide a second region in a portion of the object 306 that contacts the substrate 320 as shown in FIG. 2(f) and (g). This allows the object 306 and the substrate 320 to be efficiently separated by a wire saw or the like. In addition, when the object 306 includes a support 308, it is preferable to provide a second region that functions as a cutting position or the like at least in a portion of the support 308 that contacts the structure 304 and in a portion that contacts the substrate 320. This allows the support 308 to be efficiently removed by cutting, cutting, chemical etching, or the like. Furthermore, when processing the surface of the structure, it is preferable to provide a second region in a region that includes the surface of the structure 304 as shown in FIG. 4(a). This allows the surface of the structure to be efficiently cut and polished to a mirror finish (FIG. 4(b)).
[0084] (modeled object) In the present invention, it is preferable that 80% or more of the structure of the shaped object is made of crystalline matter. This makes it possible to obtain a shaped object with high mechanical strength and excellent durability. When irradiating the energy beam, at least one of the output of the energy beam, the relative position between the surface of the powder layer and the focus of the beam, and the scanning speed is changed according to the irradiation area to slow down the cooling rate during solidification, thereby obtaining an area with a high proportion of crystalline matter. In this case, the shaped object is designed and formed so that 80% or more of the volume of the shaped object after removing unnecessary parts by processing the shaped object is crystalline. The volume ratio of crystalline matter in the structure may be considered to be the same as the area ratio of crystalline matter derived by X-ray diffraction or electron beam diffraction of the cross section of the shaped object.
[0085] When the structure of the present invention is analyzed at two or more points near the center of any cross-section of the structure, it is preferable that crystalline and amorphous portions are present at each of the analyzed points, and that 80 volume % or more of the structure is composed of crystalline portions.
[0086] Furthermore, the crystalline material preferably has a phase-separated structure consisting of two or more phases. The phase-separated structure suppresses crack propagation, thereby further improving the mechanical strength of the three-dimensional object. The presence or absence of a phase-separated structure can be easily examined using SEM-EBSD or the like.
[0087] As shown in Fig. 4(b), the second region may remain on the surface of the processed object 307. When a strong impact is applied to a structure made of a polycrystalline inorganic compound, the bonds at the grain boundaries are broken, the crystal grains are removed, and chips may occur on the surface of the processed object. The presence of the second region on the surface of the processed object 307 has the effect of suppressing chipping. EXAMPLES
[0088] The method for producing a three-dimensional structure and the three-dimensional structure of the present invention will be described in detail below with reference to examples, but the present invention is not limited to the following examples in any way. The following Examples 1 to 8 are examples in which a region having a high crystalline content and a region having a high amorphous content are created by changing the amount of heat input per unit area by changing the laser scanning speed.
[0089] <Example 1> α-Al2O3 powder, Gd2O3 powder, Tb2O 3.5 Prepare powder (Tb4O7 powder) with a molar ratio of Al2O3:Gd2O3:Tb2O 3.5 The powders were weighed out so that the ratio of the powders was 77.4:20.8:1.8. The weighed powders were ground and mixed in a wet ball mill using ethanol as a solvent for 24 hours, and then the ethanol was removed to obtain a mixed powder (material powder).
[0090] Next, the object of Example 1 was formed through steps basically similar to those shown in FIG. First, a 20 μm thick powder layer of the mixed powder was formed on an alumina substrate using a roller. Next, a Yb fiber laser (λ=1070 nm) was irradiated onto the powder layer using a laser processing machine using YLR-300-SM (product name; manufactured by IPG Photonics Japan Co., Ltd.) to melt / solidify the mixed powder. The laser output was 30 W, the irradiation diameter was 100 μmφ, and the scan speed was 200 mm / s. The relative position between the surface of the powder layer and the focal point of the laser can be adjusted by the height of the stage on which the substrate and powder layer are placed. In this example, the stage height was set to a position -1.0 mm from the focal position. 50 lines with a length of 5 mm were formed in parallel at a pitch of 100 μm to form a square modeled part with a side of about 5 mm (see FIG. 6(a)). Next, a 20 μm thick powder layer was formed with a roller so as to cover the modeled part. The laser was irradiated to the powder layer directly above the line in a manner perpendicular to the line, and 50 lines were similarly formed. By repeating this process, a molded object 306 was formed on the substrate 320, in which a total of 10 molded layers were integrated, as shown in Figure 6(b).
[0091] The input heat Q per unit area was calculated from the laser irradiation conditions and found to be approximately 19 J / mm 2 ] was the case.
[0092] Next, the powder in the non-modeled portion was removed, and model 306 integrated with substrate 320 was embedded in resin, and a rough cross section was obtained with a diamond blade. The rough cross section obtained was polished with waterproof abrasive paper and diamond slurry, and then chemically etched with an alkaline solution to give it a mirror-like surface.
[0093] The obtained cross-sectional sample was fixed to the sample stage of the SEM with conductive paste, and a carbon film of about 3 nm was evaporated onto the polished surface, followed by SEM observation, EBSD analysis, and energy dispersive X-ray spectroscopy (EDX) analysis.
[0094] The thickness of the molded object 306 was approximately 62 μm. The cross section had irregularities formed by polishing and chemical etching. Multiple SEM images were taken, and the ratio of concave and convex areas in the entire cross section of the molded object (approximately 60 μm × approximately 5 mm) was examined. As a result, of the entire cross section of the molded object excluding voids, 88% by area was concave and 12% by area was convex. In addition, the porosity of the cross section of the molded object was calculated from the same SEM images, and when the entire cross section of the molded object including voids was taken as 100% by area, the porosity was 3% by area. Figure 9 shows an SEM image of the polished surface.
[0095] Next, EBSD analysis was performed on the cross section of the molded object. Two types of Kikuchi patterns, corundum structure and perovskite structure, were detected from the convex parts. In other words, it was found that the convex parts are crystalline and have a phase-separated structure consisting of a corundum structure phase and a perovskite structure phase. On the other hand, a Kikuchi pattern could not be obtained from the concave parts. This result indicates that the concave parts are amorphous. Furthermore, EDX analysis of the convex parts detected Al and O from the corundum structure phase, and Gd, Tb, Al, and O from the perovskite structure phase. In other words, it was found that the convex parts are composed of α-Al2O3 and (Gd,Tb)AlO3.
[0096] <Example 2> A molded object was formed in the same manner as in Example 1, except that the laser scanning speed was set to 50 mm / s. The input heat amount Q per unit area was calculated from the laser irradiation conditions, and Q was found to be approximately 76 [J / mm 2 ] was the case.
[0097] The obtained molded product was analyzed in the same manner as in Example 1. The thickness of the molded product was approximately 60 μm. Of the cross-sectional area of the molded product excluding voids, 98 area % was convex and 2 area % was concave. EBSD analysis showed that the convex parts were crystalline and the concave parts were amorphous. EBSD analysis and EDX analysis showed that the crystalline part had a phase-separated structure consisting of α-Al2O3 and (Gd,Tb)AlO3. Furthermore, when the cross-sectional area of the molded product including voids was taken as 100 area %, the porosity was 5 area %.
[0098] <Example 3> A molded object was formed in the same manner as in Example 1, except that the laser scanning speed was set to 100 mm / s. The input heat amount Q per unit area was calculated from the laser irradiation conditions, and Q was found to be approximately 38 [J / mm 2 ] was the case.
[0099] The obtained molded product was analyzed in the same manner as in Example 1. The thickness of the molded product was approximately 61 μm. Of the cross-sectional area of the molded product excluding voids, 34 area % was convex and 66 area % was concave. EBSD analysis showed that the convex parts were crystalline and the concave parts were amorphous. EBSD analysis and EDX analysis showed that the crystalline part had a phase-separated structure consisting of α-Al2O3 and (Gd,Tb)AlO3. Furthermore, when the cross-sectional area of the molded product including voids was taken as 100 area %, the porosity was 4 area %.
[0100] <Example 4> A molded object was formed in the same manner as in Example 1, except that the laser scanning speed was set to 150 mm / s. The input heat amount Q per unit area was calculated from the laser irradiation conditions, and Q was found to be approximately 25 [J / mm 2 ] was the case.
[0101] The obtained molded product was analyzed in the same manner as in Example 1. The thickness of the molded product was approximately 62 μm. Of the cross-sectional area of the molded product excluding the area of voids, 15 area % was convex and 85 area % was concave. EBSD analysis showed that the convex parts were crystalline and the concave parts were amorphous. EBSD analysis and EDX analysis showed that the crystalline part had a phase-separated structure consisting of α-Al2O3 and (Gd,Tb)AlO3. Furthermore, when the cross-sectional area of the molded product including the voids was taken as 100 area %, the porosity was 3 area %.
[0102] The results of Examples 1 to 4 are shown in Figure 7. The graph in Figure 7 shows the input heat quantity Q [J / mm 2The relationship between Q and C [area %] (horizontal axis) and the proportion of crystalline matter C [area %] (vertical axis) is shown. Q and C are roughly proportional to each other and can be approximated by a relational expression such as C=A×Q+B (where A and B are constants). From the results of Examples 1 to 4, an approximation expression for the relationship between Q and C was derived using the least squares method, and the approximation expression C=1.4×Q-17 (hereinafter referred to as Equation 1) was obtained.
[0103] <Example 5> A molded object was formed in the same manner as in Example 1, except that α-Al2O3 powder was used as the inorganic compound powder, the Yb laser output was set to 40 W, and the laser scanning speed was set to 40 mm / s. The input heat amount Q per unit area was calculated from the laser irradiation conditions, and Q was found to be approximately 127 [J / mm 2 ] was the case.
[0104] The obtained molded product was analyzed in the same manner as in Example 1. The thickness of the molded product was about 67 μm. Of the entire cross section of the molded product excluding voids, 84 area % was convex and 16 area % was concave. EBSD analysis showed that the convex parts were crystalline and the concave parts were amorphous. EBSD analysis and EDX analysis showed that the crystalline part was α-Al2O3. Furthermore, when the entire cross section of the molded product including voids was taken as 100 area %, the porosity was 5 area %.
[0105] <Example 6> A molded object was formed in the same manner as in Example 5, except that the laser scanning speed was set to 80 mm / s. The input heat Q per unit area was calculated from the laser irradiation conditions, and Q was found to be approximately 64 [J / mm 2 ] was the case.
[0106] The obtained molded object was analyzed in the same manner as in Example 5. The thickness of the molded object was approximately 66 μm. Of the cross-sectional area of the molded object excluding the voids, 28 area % was convex and 72 area % was concave. EBSD analysis showed that the convex parts were crystalline and the concave parts were amorphous. EBSD analysis and EDX analysis showed that the crystalline part was α-Al2O3. Furthermore, when the cross section including the voids of the molded object was taken as 100 area %, the porosity was 4 area %.
[0107] <Example 7> A molded object was formed in the same manner as in Example 5, except that the laser scanning speed was set to 160 mm / s. The input heat Q per unit area was calculated from the laser irradiation conditions, and Q was found to be approximately 32 [J / mm 2 ] was the case.
[0108] The obtained molded product was analyzed in the same manner as in Example 5. The thickness of the molded product was approximately 66 μm. Of the cross-sectional area of the molded product excluding the area of voids, 8 area % was convex and 92 area % was concave. EBSD analysis showed that the convex parts were crystalline and the concave parts were amorphous. EBSD analysis and EDX analysis showed that the crystalline part was α-Al2O3. Furthermore, when the cross section of the molded product including voids was taken as 100 area %, the porosity was 4 area %.
[0109] <Example 8> A molded object was formed in the same manner as in Example 5, except that the laser scanning speed was set to 200 mm / s. The input heat Q per unit area was calculated from the laser irradiation conditions, and Q was found to be approximately 25 [J / mm 2 ] was the case.
[0110] The obtained molded product was analyzed in the same manner as in Example 5. The thickness of the molded product was approximately 66 μm. Of the cross-sectional area of the molded product excluding the area of voids, 1 area % was convex and 99 area % was concave. EBSD analysis showed that the convex parts were crystalline and the concave parts were amorphous. EBSD analysis and EDX analysis showed that the crystalline part was α-Al2O3. Furthermore, when the cross-sectional area including the area of voids of the molded product was taken as 100 area %, the porosity (area of voids) was 3 area %.
[0111] The results of Examples 5 to 8 are shown in FIG. 8. From the graph in FIG. 8, the input heat amount Q [J / mm 2 The relationship between Q and the crystalline fraction C [area %] was derived, and the approximate formula C = 0.81 × Q-20 was obtained.
[0112] Although a laser was used in Examples 1 to 8, an electron beam can also be used. In addition to the scanning speed, the amount of heat input per unit area can also be changed by changing the irradiation diameter and output (in the case of an electron beam, the acceleration voltage and beam current instead of the output) to create crystalline and amorphous materials.
[0113] <Comparative Example 1> A model was formed in the same manner as in Example 1, except that the laser scanning speed was set to 5 mm / s. As a result, the input heat amount per unit area was about 764 [J / mm 2 ] was too large, causing the mixed powder to melt over a wide area, significantly reducing the molding accuracy.
[0114] <Comparative Example 2> A model was formed in the same manner as in Example 1, except that the laser scanning speed was set to 1000 mm / s. As a result, the amount of heat input per unit area was about 4 [J / mm 2 ] was too small, resulting in insufficient melting / solidification of the mixed powder.
[0115] <Comparative Example 3> A model was formed in the same manner as in Example 5, except that the laser scanning speed was set to 5 mm / s. As a result, the input heat amount per unit area was about 1019 [J / mm 2 ] was too large, causing the mixed powder to melt over a wide area, significantly reducing the molding accuracy.
[0116] <Comparative Example 4> A model was formed in the same manner as in Example 5, except that the laser scanning speed was set to 1000 mm / s. As a result, the input heat amount per unit area was about 5 [J / mm 2 ] was too small, resulting in insufficient melting / solidification of the mixed powder.
[0117] The results of Examples 1 to 8 and Comparative Examples 1 to 4 are shown in Table 1. [Table 1]
[0118] In Examples 9 to 22, crystalline and amorphous portions were produced by changing the shape of the molten portion of the material powder by changing the output of the laser beam and the relative position between the surface of the powder layer and the focal point of the laser beam.
[0119] The relative position between the surface of the powder layer and the focal point of the laser beam can be adjusted by changing the height of the stage on which the substrate or powder layer is placed. Since the state of the laser beam due to defocusing is the same whether the surface of the powder layer is on the plus side (the side closer to the scanning mirror of the laser beam) or the minus side (the side farther from the scanning mirror of the laser beam) of the stage height from the focal position, only the minus side was examined in the examples of the present invention.
[0120] <Examples 9 and 10> Spherical α-Al2O3 powder (average particle size 20 μm), spherical Gd2O3 powder (average particle size 25 μm), and Tb4O7 particles (average particle size 3 μm) were prepared and weighed to obtain a mass ratio of Al2O3:Gd2O3:Tb4O7 = 2.10:2.00:0.18. The weighed powders were mixed in a dry ball mill for 30 minutes to obtain a mixed powder (material powder).
[0121] To investigate the amount of organic components contained in this mixed powder, the powder was heated in an electric furnace at 400°C for 12 hours and the weight change before and after was measured, and the weight loss was less than 0.5% by weight.The powder was also heated in an electric furnace at 800°C for 12 hours and the weight change before and after was measured, and the weight loss was less than 1.0% by weight.
[0122] To form the object, a 3D SYSTEMS ProX DMP 100 (product name) equipped with a 50 W fiber laser (beam diameter: 65 μm) was used.
[0123] First, a roller was used to form a first powder layer of the material powder with a thickness of 30 μm on an alumina substrate. Next, the sample of Example 9 was placed on a part of the alumina substrate, and the sample of Example 10 was placed on the same base so as not to overlap. In the sample of Example 9, a 20 W laser beam was irradiated to the powder layer at a focused position (stage height -1.5 mm in this embodiment) at a speed of 100 mm / s so as to fill in a 6 x 6 mm square area at a pitch of 100 μm, and melted / solidified (second scanning stage). On the other hand, in Example 10, a 30 W laser beam was irradiated to the powder layer at a non-focused position (stage height -5.0 mm in this embodiment) at a speed of 140 mm / s so as to fill in a 6 x 6 mm square area at a pitch of 100 μm, and melted / solidified (first scanning stage). In addition, the drawing lines were made parallel to each side of the square. Next, a new powder layer of 20 μm thickness was formed with a roller so as to cover the melted and solidified parts. The powder layer directly above the square area of the sample of Example 9 and the sample of Example 10 was irradiated with a laser under the same conditions as above, so as to be perpendicular to the drawing line of the first layer, and the powder within an area of 6 × 6 mm was melted and solidified. Note that from the second layer onwards, the thickness of the powder layer was kept constant at 20 μm.
[0124] By repeating this process (iii), each object was formed with a base of 6 mm × 6 mm and a height of 6 mm. The drawing procedure was such that the drawing line was rotated by 90° as the nth layer was layered, followed by the n+1th layer, the n+2th layer, and the n+3th layer, until the object reached the desired thickness.
[0125] The molded objects of Examples 9 and 10 were separated from the alumina substrate, and cut and polished in a vertical plane parallel to the side surface when the connection part with the substrate was the lower surface, to prepare a specimen for observation. The observation was performed by EBSD, and an IQ map image was obtained. The IQ map is a two-dimensional image obtained by quantifying the sharpness of the Kikuchi pattern obtained from the area irradiated with the electron beam. At this time, a signal is obtained from the crystalline area, but no signal is obtained in the case of amorphous, so it can be used to distinguish which parts of the molded object are amorphous and which are crystalline.
[0126] The proportion of crystalline matter in the observation field of Example 9 was 20 area %. The proportion of crystalline matter in the observation field of Example 10 was 96 area %.
[0127] In order to measure the molten shape of the powder layer when irradiated with the laser beam, a powder layer with a thickness of 30 μm was formed on a base in the same manner as when the molded object of Example 9 was produced, and the powder layer was irradiated with a laser beam under the irradiation conditions of Example 9 in a straight line. The cross-sectional shape of the line melted and solidified by the irradiation was observed, and the shape was quantified by the ratio D / L of the width (L) and depth (D) perpendicular to the line of the melted / solidified part that was embedded in the alumina substrate. Under the conditions of Example 9, D / L was 1.29, and when a line was similarly drawn under the conditions of Example 10 and the cross-sectional shape was evaluated, D / L was 0.32.
[0128] <Examples 11 to 22> The stage height, laser beam output, and scan speed were set under the conditions shown in Table 2, and objects of Examples 11 to 22 were produced and evaluated in the same manner as in Example 9. The D / L value and the proportion of crystalline matter for each Example are shown in Table 2.
[0129] <Comparative Example 5> An attempt was made to manufacture and evaluate a comparative object for comparison in Comparative Example 5 in the same manner as in Example 9, except that the stage height was -7.0 mm, the laser beam output was 20 W, and the scan speed was 100 mm / s. As a result, under the conditions of this comparative example, the material powder did not melt sufficiently, and it was not possible to draw lines or manufacture a model.
[0130] [Table 2]
[0131] <Consideration> As in Examples 1 to 8, the amount of heat input per unit area is adjusted by changing the scanning speed of the laser beam, and the cooling rate during solidification is controlled, thereby making it possible to selectively produce crystalline and amorphous materials.
[0132] As in Examples 9 to 22, the melt shape (D / L) can be controlled by changing the output and focal position of the laser beam, and the cooling rate during solidification can be controlled to produce either crystalline or amorphous material.
[0133] In Examples 9, 11, and 12, the laser beam was irradiated in a focused state, resulting in a D / L of 1.2 or more, a low crystalline proportion of 20 area % or less, and a high amorphous proportion.
[0134] In Examples 13 to 16 and 21, the laser beam was irradiated in a defocused state, resulting in a D / L of less than 1.0 and a high crystalline ratio of 70% or more by area. In Examples 13 to 16, the D / L was less than 0.7 and the crystalline ratio was high, 80% or more.
[0135] Although the focal positions are the same in Examples 17 and 18, Example 17, which has a low laser beam output, has a high crystalline fraction, while Example 18, which has a high output, has a low crystalline fraction.
[0136] For example, by forming a support under the conditions of Example 9 and forming a shaped object under the conditions of Example 10, the support can be removed efficiently.
[0137] In addition, by melting / solidifying the powder layer directly on the substrate under conditions such as those in Example 9, and then producing a molded object on top of it under conditions such as those in Example 10, it is possible to efficiently separate the substrate and the molded object.
[0138] Furthermore, by forming the surface layer of the molded object under the conditions of Example 9 and the inside of the molded object under the conditions of Example 10, it is possible to obtain a molded object whose inside is crystalline and whose surface layer is amorphous. This makes it easier to process the surface layer of the molded object while ensuring the strength of the object, and has the effect of suppressing the phenomenon of crystal grains chipping at grain boundaries when the inside of the molded object is polycrystalline.
[0139] The present invention can be realized by having a three-dimensional printing device execute each of the above-mentioned steps, such as the first step of forming a powder layer made of a material powder containing an inorganic compound powder, and the second step of irradiating an energy beam to melt / solidify the material powder. Specifically, a program for implementing the operation of the above-mentioned embodiment is supplied to a system including the three-dimensional printing device or the three-dimensional printing device via a network or various storage media. Then, a computer (such as a CPU) of the system including the three-dimensional printing device or the three-dimensional printing device reads out the program and has the three-dimensional printing device execute it. [Industrial Applicability]
[0140] INDUSTRIAL APPLICABILITY The present invention can be utilized as a method for manufacturing a shaped object in a direct manufacturing method, which is capable of efficiently removing unnecessary portions of the shaped object while achieving a desired strength of the shaped object. [Explanation of symbols]
[0141] 300 Modeling Department 301 Material powder 302 Powder layer 304 Structure (modeling part) 306 Modeled objects 307 Processed objects
Claims
1. forming a three-dimensional object having a first region including a crystalline material and a second region including an amorphous material; and processing the three-dimensional object, The shaping step includes: forming a first powder layer made of a material powder including an inorganic compound powder; irradiating a first portion of the first powder layer with an energy beam to form the first region from the powder of the inorganic compound in the first portion; forming a second powder layer made of a material powder containing a powder of the inorganic compound; irradiating a second portion of the second powder layer with an energy beam to form the second region from the powder of the inorganic compound in the second portion; Including, The first region has a higher proportion of crystalline crystals than amorphous crystals per unit area, the proportion of the amorphous material is greater than the proportion of the crystalline material per unit area in the second region; The unit area of the first region and the unit area of the second region are 100 μmφ or more, The manufacturing method according to claim 1, wherein in the processing step, the second region is processed to remove the second region from the three-dimensional object so that the article includes the first region.
2. The method according to claim 1 , wherein the inorganic compound is an oxide.
3. The method according to claim 1 or 2, wherein at least a portion of a surface of the three-dimensional structure includes a region having a high proportion of the amorphous material.
4. The method according to any one of claims 1 to 3, wherein the three-dimensional structure has a recess formed in the region where the proportion of amorphous matter is high.
5. The method according to any one of claims 1 to 4, wherein the three-dimensional structure has a convex portion formed in an area where the proportion of the crystalline material is high.
6. The method according to any one of claims 1 to 5, wherein the crystalline content of the region with a high crystalline content is 80% by volume or more.
7. The method according to any one of claims 1 to 6, wherein the amorphous content of the amorphous-rich region is 70 volume % or more.
8. The method according to any one of claims 1 to 7, wherein the inorganic compound is aluminum oxide.
9. The method according to any one of claims 1 to 7, wherein the inorganic compound is zirconium oxide.
10. The method according to any one of claims 1 to 7, wherein the inorganic compound is silicon oxide.
11. The method according to any one of claims 1 to 7, wherein the inorganic compound is a rare earth oxide.
12. The method according to any one of claims 1 to 11, wherein the region with a high proportion of crystalline matter has a phase-separated structure having two or more phases.
13. The method according to any one of claims 1 to 12, wherein the region with a high crystalline content has a eutectic composition.
14. The method according to any one of claims 1 to 13, wherein the three-dimensional object has a thickness of 20 µm or more.
15. The method according to any one of claims 1 to 14, wherein a unit area of the first region and a unit area of the second region are 200 µmφ or more.
16. The method according to any one of claims 1 to 14, wherein a unit area of the first region and a unit area of the second region are 1 mm2 or more.
17. The method according to any one of claims 1 to 16, wherein the three-dimensional object is formed of a plurality of phases bonded together.
18. The method according to any one of claims 1 to 17, wherein the three-dimensional object has a void.
19. The method according to any one of claims 1 to 18, wherein the three-dimensional object is produced by a direct modeling method.
20. The method according to any one of claims 1 to 19, wherein the three-dimensional object is produced by a bed fusion bonding method.
21. The method according to claim 1 , wherein the step of forming the first powder layer is performed after the step of forming the second region.
22. the second powder layer is formed on a substrate; The region with a high amorphous ratio formed in the step of forming the second region is 22. The method according to claim 1, wherein the first region is located between the region having a high crystalline content formed in the step of forming the first region and the substrate.
23. 23. The method according to claim 22, wherein the processing step includes a step of separating the structure having the region with a high proportion of crystalline matter formed in the step of forming the first region from the substrate.
24. 24. The method according to claim 23, wherein the separation is performed using the region with a high amorphous content formed in the step of forming the second region.
25. The manufacturing method according to any one of claims 1 or 21 to 24, further comprising a step of removing the material powder in a third portion of the second powder layer after the step of forming the second region, wherein in the step of removing the material powder in the third portion, the second region is in contact with the third portion.
26. irradiating a fourth portion of the first powder layer with an energy beam; The manufacturing method according to any one of claims 1 or 21 to 25, characterized in that in the step of irradiating the fourth portion with an energy beam, a fourth region having a high amorphous ratio is formed from the powder of the inorganic compound in the first powder layer.
27. 27. The method of claim 26, wherein the fourth portion includes a plurality of portions, and the region having a high crystalline content formed in the step of forming the first region is located between the plurality of portions.
28. 28. The manufacturing method according to claim 26 or 27, further comprising, after the step of forming the first region, a step of removing the material powder in a fifth portion of the first powder layer, wherein in the step of removing the material powder in the fifth portion, the fifth portion is located between the first region and the fourth region.
29. 28. The manufacturing method according to claim 26 or 27, further comprising a step of removing the material powder in a fifth portion of the first powder layer after the step of forming the first region, wherein in the step of removing the material powder in the fifth portion, the fourth region is located between the first region and the fifth portion, and the fourth region is in contact with the first region and the fifth portion.
30. 30. The manufacturing method according to any one of claims 1 or 21 to 29, characterized in that the object is formed in a state bonded to a substrate, and a region with a high amorphous ratio is provided at a cutting position when separating the object from the substrate.
31. 31. The method of claim 1, further comprising the step of removing the region with a high amorphous content.
32. 32. The method of claim 31, wherein the article after the step of removing the amorphous-rich regions is at least 80% crystalline by volume.
33. The method according to any one of claims 1 or 21 to 32, characterized in that the powder of the inorganic compound includes a ceramic powder.
34. The manufacturing method according to any one of claims 1 or 21 to 33, characterized in that the powder of the inorganic compound contains at least two of aluminum oxide, zirconium oxide, magnesium oxide, and silicon oxide, or at least two of aluminum oxide, zirconium oxide, a first rare earth oxide, and a second rare earth oxide.
35. The method according to any one of claims 21 to 34, wherein the region with a high amorphous content is amorphous in an amount of 70 volume % or more.
36. The method according to any one of claims 21 to 35, characterized in that 80% by volume or more of the region with a high crystalline content is crystalline.
37. The method according to any one of claims 21 to 36, characterized in that the crystalline material has a phase-separated structure consisting of two or more phases.
38. 38. The method of claim 1, wherein the energy beam is a laser beam or an electron beam.
Citation Information
Patent Citations
The method of manufacturing components of sintered selectively
JP1989502890A
Method for producing three-dimensionally shaped object
JP2008291315A
Method of producing laminated molding
JP2015196249A
Glass powder for three-dimensional molding
JP2017071532A
Flowable composition set and flowable composition
JP2017075366A